Manajemen Pembinaan Tenaga Kependidikan pada bidang pendidikan madrasah di kantor kementerian agama kota palangka raya - Norafnan, Abdul; Fahmi; Riyadi, Slamet (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2025)
This research aims to identify and evaluate the management of educational staff development in the field of madrasah education at the Ministry of Religious Affairs Office in Palangka Raya. The main focus of this study is to understand how the development of educational staff is carried out in madrasahs and the factors that influence its success. The research approach used is qualitative with a field research method, relying on interviews, observations, and document collection as data collection techniques. The results of the study show that the management of educational staff development in madrasahs is carried out through systematic and structured stages of planning, implementation, and evaluation. The development program designed aims to improve the competence and quality of educational staff, with an emphasis on mastering educational technology and administrative skills. Evaluation of the development program indicates a positive impact on the improvement of technical skills, but also identifies several challenges that need to be addressed, such as the need to adjust training materials and strengthen supervision over the application of development results. Based on these findings, the study suggests that development should focus more on the enhancement of managerial and social skills, as well as strengthening mentoring and coaching programs in the future.